The Impact of Modern Models on Strategic Human Resources Management on Promoting Organizational Agility for Institutions, Analytical and Descriptive Study - Al- Rakhis, Maha Mohammad; Al- Rakhis, Fatima Mohammad (Journal of Economic, Administrative and Legal Sciences, 2020)
The study aimed to identify the impact of modern models of strategic human resource management on enhancing organizational agility for institutions, and by relying on the descriptive analytical approach to the previous literature in this field through four hypotheses that were discussed, it was clear from the results of the study that there is a relationship between modern models of strategic human resource management on Strengthening organizational agility and validating the four assumptions, the study recommended preparing and implementing a human resources strategy based on the dimensions of the four models, aligning and amending human resource management policies in a manner that achieves facilitation and facilitation of wages Categories according to staff in the performance of the strategic models of human resources management, development work harmoniously with the organizational agility environment.
Keywords: Strategic Human Resource Management; Strategic Alignment Model; High Performance Model; High Commitment Model; Organizational Agility; Best Practices Model